The Effectiveness of The Merdeka Mengajar Platform PMM in Supporting The Pedagogical Competence of Early Childhood Education PAUD Teachers in North Minahasa - Tewuh, Adeleide Alfiani; Puridawaty, Brigita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to determine the effectiveness of the Merdeka Mengajar Platform (PMM) in supporting the pedagogical competence of Early Childhood Education (PAUD) teachers in North Minahasa. The researcher employed a quantitative (survey) method by distributing questionnaires to PAUD teachers in North Minahasa. With a sample size of 200 PAUD teachers, the results showed that the highest percentage—73.34% or 146 teachers—fell into the medium category of understanding, followed by 27 teachers (13.33%) with low understanding, and only 27 teachers (13.33%) with high understanding. Therefore, the effectiveness of the Merdeka Mengajar Platform (PMM) in supporting the pedagogical competence of PAUD teachers in North Minahasa is categorized as Moderate.